Indonesian Learning and Think Pair Share Model: An Effort to Improve Student Learning Outcomes - Adrianus Tambing Bontong; Karlina Wong Lieung; Martha Betaubun; Hendrika Walten (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to apply the Think Pair Share learning model as an effort to improve student learning outcomes in Indonesian language learning. This research uses a type of classroom action research, which is one of the problem-solving strategies that utilizes real action from the process of detecting problem-solving abilities. The design used in this study is the Kemmis and Mc. Taggart model. The approach used in this study is a qualitative approach, but to complete the data also used qualitative data. This research step is carried out in 2 cycles and each cycle consists of 2 meetings. Each cycle consists of stages of planning, action, observation and reflection. Data collection using observation sheets, tests and documentation. The results showed that the application of the Think Pair Share learning model using can improve activities and learning outcomes Indonesian grade II students. The average score for student graduation criteria starting from pre-cycle on was 60.7%, which then increased by 9.95% in cycle I and became 70.65%. Meanwhile, the percentage of student graduation increased in the second cycle, which was 18.77% and became 89.42%. This increase proves that the TPS (Think Pair Share) learning model in Indonesian learning can improve the learning outcomes of grade II students.